Hierarchical Organization of Gamma and Theta Oscillatory Dynamics in Schizophrenia - Kirihara, Kenji; Rissling, Anthony J.; Swerdlow, Neal R.; Braff, David L.; Light, Gregory A. (Biological psychiatry (1969), 2012)
Schizophrenia patients have deficits across a broad range of important cognitive and clinical domains. Synchronization of oscillations in the gamma frequency range (∼40 Hz) is associated with many normal cognitive functions and underlies at least some of the deficits observed in schizophrenia patients. Recent studies have demonstrated that gamma oscillations are modulated by the phase of theta waves, and this cross-frequency coupling indicates that a complex and hierarchical organization governs neural oscillatory dynamics. The aims of the present study were to determine if schizophrenia patients have abnormalities in the amplitude, synchrony, and cross-frequency coupling of gamma and theta oscillations in response to gamma-frequency steady-state stimulation and if abnormal neural oscillatory dynamics are associated with cognitive deficits in schizophrenia. Schizophrenia patients (n = 234) and healthy control subjects (n = 188) underwent electroencephalography testing in response to 40-Hz auditory steady-state stimulation. Cognitive functions were assessed with a battery of neuropsychological tests. Schizophrenia patients had significantly reduced gamma intertrial phase coherence, increased theta amplitude, and intact cross-frequency coupling relative to healthy control subjects. In schizophrenia patients, increased theta amplitude was associated with poor verbal memory performance. Results suggest that schizophrenia patients have specific alterations in both gamma and theta oscillations, but these deficits occur in the context of an intact hierarchical organization of their cross-frequency modulation in response to 40-Hz steady-state stimulation. Cortical oscillatory dynamics may be useful for understanding the neural mechanisms that underlie the disparate cognitive and functional impairments of schizophrenia.